Implementation of Gamification With Kahoot Platform! in Improving Student Learning Achievement UPBJJ UT Semarang - Kadarwati, Sri; Sulistyarini, Ika; Prayitno, Edi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research is to find out whether the learning achievements of UPBJJ UT Semarang PGSD students can be improved through the use of gamification with the Kahoot platform! integrated with Ms. Teams in Tuweb. In this study, researchers implemented Gamification with the Kahoot platform! which is used as an effort to improve learning achievement in the English learning process for elementary teachers. The subject in this study is a student of S1 PGSD Semester 1 (one) UPBJJ UT Semarang Registration Period 2021.1 Pokjar Kaliwungu Kendal number of 24 students. This study is a 2-cycle Classroom Action Research with 1 pre-test and 2 post-tests through the stages of planning, action, observation, and reflection. From the results of the study showed an increase in the learning achievement of S1 PGSD UPBJJ UT Semarang students through the use of gamification with the Kahoot platform! integrated with Ms. Teams in Tuweb. This is characterized by an average increase in the score from pre-test to post-test 1 by 27.81 points (from 47.40 to 75.21). Furthermore, there was also an average increase in the score from post-test 1 to post-test 2 by 11.35 points (from 75.21 to 86.56). Based on the findings and conclusions can be proposed that gamification with kahoot platform! Integrated with Ms. Teams in Tuweb can be used as an alternative in the implementation of the teaching and learning process in the situation of the Covid-19 pandemic that requires learning to be done online or remotely.